(untitled) (Journal of Applied Learning and Teaching, 2025)
This paper explores the role theorizing non-western ontologies play in developing pedagogies that center on animist praxis as a valid and necessary approach to problematizing environmental challenges in the environmental sciences and humanities. The ongoing call for this transdisciplinary pedagogical approach continues to suggest that the challenge of the Anthropocene is an ontological challenge arising from modern humans’ abstraction from a more-than-human planetary community – rooted in the substance ontology of Euro-Cartesian metaphysics. The central focus of this pedagogy seeks to understand how theoretical examination of and self-reflexive engagement with the metaphysics of animist ontologies dismantle the primacy of dominant Euro-Cartesian assumptions in the classroom about the nature of reality and nature-knowledge relationships that inform systemic practices of environmental control. In privileging Indigenous and Earth-centered epistemologies, this paper suggests how a pedagogy based on animist and other relational ontologies can assist students in experiencing themselves as part of an ecological web that values transspecies agencies – examining how theorizing and critical reflection on animist understandings of personhood, kinship, and the ambiguity of ontological between species can radically alter students’ approaches to environmental work and reshape their relationships with other species.